Salafi-Based Integrated Islamic Elementary School Management - Erwandi, Rudi; Prananosa, Ahmad Gawdy; Putra, M Rusni Eka; Yuneti, Armi; Pestalozi, Donni (Tafkir: Interdisciplinary Journal of Islamic Education, 2023)
The research aims at investigating the management of Salafi-based integrated Islamic schools. This research employed a qualitative approach with phenomenological methods. This research was conducted at Raudatul Jannah Integrated Islamic Elementary School, Lubuklinggau City. The research subjects consisted of the principal, teacher council, and school staff. The data were collected using interviews. The collected data were then analyzed by adapting the technique from Miles & Huberman, namely the interactive analysis model. The research results signified that the Salafi Integrated Islamic Elementary School has carried out planning, organizing, implementing, and evaluating for students, teachers, and educational staff, curriculum, facilities and infrastructure, finance, and public relations appropriately, such as: 1) The school has carried out planning activities, particularly for students, teachers, and educational staff, curriculum, facilities and infrastructure, finance, and community relations; 2) The school has implemented organizing activities for students, in which male and female students are put into separate classes, and male and female teachers or educational staff are also given separate rooms; 3) The school implements the independent curriculum for grades 1 and 4, then the curriculum from the Ministry of Religious Affairs and the Ministry of National Education for grades 2, 3, 5, and 6; 4) In the implementation of evaluations, the school creates self-prepared examinations, which are not from the National Education Department.